Literacy for the 21st century : An overview & orientation guide to media literacy education - Thoman, Elizabeth; Jolls, Tessa (Center for Media Literacy, 2005)
This publication constitutes a complete framework for critical inquiry for both construction and deconstruction of media, along with handouts. Also, it gives explanations and guiding questions to illustrate how to connect the key questions when consuming or producing or participating with media and provides in-depth explanations and the foundational role of the five key questions of media literacy. Teachers can find here a sample inquiry into visual language: "How to Conduct a 'Close Analysis' of a Media Text".
Keywords: enseignement; literacy; média